HUBUNGAN ANTARA KARAKTERISTIK PETERNAK KAMBING KALIGESING DENGAN PERSEPSI PETERNAK TERHADAP PERAN PENYULUH DALAM MANAJEMEN PEMELIHARAAN DI KECAMATAN KALIGESING KABUPATEN PURWOREJO - , WAHYUDI, S.Pt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this research were to describe the characteristics of Kaligesing goat farmers , know farmersâ perceptions on the role of extension workers as conduit of information, as mentors , as organizers and dynamic factor, as technicians and as liaisons, knowing the relationship between the farmersâ characteristics with farmersâ perceptions, and to investigate the relationship between farmersâ perceptions with maintenance management . The respondents were goat farmers in Kaligesing district, Purworejo Regency, Central Java. The data were gained through questionnaire survey method. Determining location, the research applied combination of stratified sampling method with purposive random sampling. The samples farmer groups used random sampling and determination of farmers as respondents used convenience sampling. Number of farmer groups as samples were nine groups and the total number of respondents were 159 farmers. This research used Spearman Rank analysis to analyze the relationship between farmersâ characteristics with farmersâ perceptions to the role of the extension workers, and also to analyze their relation to maintenance management. The analysis showed that age, education level and farming experience was not significant to the farmersâ perceptions to the role of extension workers, but the ownership of livestock had a high significant relationship (P<0.01) with a correlation coefficient of 0.240, group classes had a very close relationship (P<0.01) with a correlation coefficient 0.414 and frequency of meeting with extension workers have real relationships (P<0.05) with a correlation coefficient of 0.202. Farmersâ perceptions to the role of extension workers had very close relationships (P<0.01) to the maintenance management with a correlation coefficient of 0.393